Perancangan Model Prototype Sistem Informasi Pengelolaan Barang Bukti Pada Divisi PB3R Di Kejaksaan Negeri Kota Bekasi - Atanasius Jales Putra Bagaskara; Dian Permatasari (Jurnal Media Infotama, 2023)
Kejaksaan has various special fields, one of which is the field of Evidence and Confiscated Goods. This field has the task of managing data and storing evidence of cases, but the existing data management process is still not effective because data management is still done manually. In the process of searching for evidence, there are often obstacles in finding the required evidence, either for the needs of the trial or to be returned to the rightful owner of the evidence. To solve the existing problems, the design of an evidence data management information system in which there are several features supporting work activities will solve the existing problems. The design of this information system uses a prototype model which includes analysis of user needs, interface design and interface display testing. With the design of an information system for managing evidence data, it has facilitated the performance of the prosecutor's staff, especially in the field of Evidence and Confiscated Goods, in managing existing evidence.